Forest transport roads according to natural forest regions in the Czech Republic - J. Žáček; P. Klč (Journal of Forest Science, 2008)
Important parts of the forest sector are forest engineering constructions and capital construction of forest road network which improve the optimal management of forests and forest stands and their reasonable opening by a forest road network. The basic frameworks of forest road network are forest transport roads of various grades and categories. The paper discusses the basic parameters of forest transport roads such as the length of forest transport roads and their density outspread to the area of a particular district above all. The conditions of forest opening in 41 Natural Forest Regions of the Czech Republic and in the Czech Republic as a whole are shown and confronted on the basis of these parameters. A dilemma of the double division of forest transport roads according to the standard ČSN 73 6108 - Lesní dopravní síť (Forest Transportation Network) and according to the methodology used by Forest Management Institute in Brandýs nad Labem is also described in the paper. Although it is not suitable to use two methods of evaluation, there is no tendency to unify it.